AN EXCEPTION TO THE CIDNP SIGN RULES - Hore, P; Stob, S; Kemmink, J; Kaptein, R (1983)
It is demonstrated experimentally that the CIDNP sign rules can give erroneous results. Net effects observed in the 1H NMR spectrum of 1-phenyl[2-13C]propan-2-one after photolysis are correctly predicted at 360 MHz but not at 100 MHz by the rules. The converse is true for the 1H-13C multiplet effects. The radical pair theory can account for the CIDNP effects in all cases. © 1983.